Talk. Show - Meyer-Büser, Susanne,Brock, Bazon,Darsow, Götz-Lothar (Prestel, 1999)
Ausstellungskatalog
Keywords: Ausstellungskatalog; Konferenzschrift; Mass media and art; Communication in art; Multimedia (Art); Interactive art